Low-clinker cement-based concrete, decorative concrete member and application

By using less clinker cement-based concrete in decorative concrete components, combined with the use of red mud, slag, crack-resistant fibers and nano-oxides, the problems of high energy consumption, carbon emissions and poor crack resistance of decorative concrete components in production and use are solved, and the effects of high strength, low carbon emissions and good crack resistance are achieved.

CN119797849APending Publication Date: 2025-04-11CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510023092.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing decorative concrete components are highly energy-consuming and high carbon emissions during production, and micro-cracks are easily generated due to high brittleness and poor crack resistance during use, which affects the decoration effect and strength.

Method used

Use less clinker cement-based concrete. By reducing the use of clinker cement in the gelling components, and adding red mud, slag, crack-resistant fibers and nano-oxides, the proportion of each component is adjusted to improve the strength and fluidity of the concrete.

Benefits of technology

It has achieved the reduction of clinker cement usage and reduced production carbon emissions, while improving the tensile strength and compressive strength of concrete, enhancing stability and crack resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005231969470000101
    Figure BDA0005231969470000101
Patent Text Reader

Abstract

The invention relates to low-clinker cement-based concrete, a decorative concrete member and application. The low-clinker cement-based concrete is prepared from aggregate and a gelling component, and the gelling component is prepared from the following raw materials in percentage by mass: 5-30% of clinker cement, 10-40% of red mud and 50-80% of slag, the concrete further comprises anti-crack fibers and nano oxide, and the ratio of the total mass of the anti-crack fibers and the nano oxide to the mass of the gelling component is (0.02-0.15): 1. The technical problem to be solved is how to determine a low-clinker cement-based concrete raw material, reduce the dosage of clinker cement in a gelling component and enable the prepared low-clinker cement-based concrete to have good splitting tensile strength and compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of concrete, and in particular relates to a low-clinker cement-based concrete, a decorative concrete component and applications. Background Art

[0002] At present, decorative concrete components are widely used in fields such as building construction because they can provide beautiful decoration and have durable characteristics.

[0003] The traditional production process of decorative concrete components requires a large amount of cement to provide adhesion so that the strength performance of the produced decorative concrete components is good. However, cement has the characteristics of high energy consumption and high carbon emissions in the production process. Although decorative concrete components have advantages in coloring and texture design, how to reduce the amount of cement in decorative concrete components and reduce carbon emissions in the production process so that decorative concrete can be widely used is a challenge currently faced. Furthermore, during the use of decorative concrete components, due to the defects of high brittleness and poor crack resistance, micro cracks are easily generated during construction or long-term use. The existence and expansion of these cracks will inevitably affect the decorative effect, strength and durability of decorative concrete components. Summary of the invention

[0004] The main purpose of the present invention is to provide a low-clinker cement-based concrete, decorative concrete components and applications. The technical problem to be solved is how to provide a low-clinker cement-based concrete raw material to reduce the amount of clinker cement in the cementitious component and enable the prepared low-clinker cement-based concrete to have good splitting tensile strength and compressive strength.

[0005] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical solutions. According to the low-clinker cement-based concrete proposed by the present invention, its raw materials include aggregate and cementitious component, and the cementitious component includes 5-30% clinker cement, 10-40% red mud, and 50-80% slag, taking the mass percentage of the cementitious component as 100%; the concrete also includes anti-cracking fiber and nano-oxide, and the total mass ratio of the anti-cracking fiber and the nano-oxide to the mass ratio of the cementitious component is 0.02-0.15:1.

[0006] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0007] Preferably, in the aforementioned concrete, the mass percentage of Al2O3 in the red mud is 8-25%, and the mass percentage of SiO2 is 15-30%; the clinker cement is silicate clinker cement; and the slag is water-quenched slag.

[0008] Preferably, in the aforementioned concrete, the anti-cracking fiber is selected from at least one of polypropylene fiber, polyvinyl alcohol fiber and basalt fiber; and the nano-oxide includes nano-titanium dioxide and / or nano-silicon dioxide.

[0009] Preferably, in the aforementioned concrete, the ratio of the mass of the aggregate to the mass of the anti-cracking fiber is 64-520:1.

[0010] Preferably, in the aforementioned concrete, the aggregate comprises coarse aggregate and fine aggregate; the particle size range of the coarse aggregate is 5 to 25 mm; the fine aggregate is machine-made sand or river sand with a fineness modulus of 2.4 to 2.8; and the length of the anti-cracking fiber is 6 to 25 mm.

[0011] Preferably, in the aforementioned concrete, the mass of the coarse aggregate with a particle size of 5mm≤D1≤10mm is m1, and the mass of the coarse aggregate with a particle size of 10mm<D2≤25mm is m2; and the ratio of m1 to m2 is 0.9-1.1:1.

[0012] Preferably, in the aforementioned concrete, the particle size range of the nano oxide is 1 to 500 nm; the mass percentage of the anti-cracking fiber is m3, the mass percentage of the nano oxide is m4, and the ratio of m3 to m4 is 1 to 3:1.

[0013] Preferably, the aforementioned concrete, wherein, by mass percentage, comprises: 8-22% cementitious component, 30-56% coarse aggregate, 25-52% fine aggregate, 2-9% water, 0.1-1.3% water reducer, 0.03-0.80% nano oxide, and 0.15-1.30% anti-cracking fiber.

[0014] The purpose of the present invention and the technical problems solved by the present invention are also achieved by adopting the following technical solutions: A decorative concrete component proposed by the present invention comprises the low-clinker cement-based concrete described in the above solution.

[0015] The purpose of the present invention and the technical problem to be solved are also achieved by the following technical solutions: A building proposed in the present invention comprises the decorative concrete component described in the above solution.

[0016] By means of the above technical solution, the low-clinker cement-based concrete, decorative concrete component and application proposed by the present invention have at least the following advantages:

[0017] 1. The present invention provides a kind of low-clinker cement-based concrete, in which a large amount of red mud and slag are added to the cementitious component in the raw materials, so as to reduce the use of clinker cement, and by limiting the mass percentage of clinker cement, red mud and slag in the cementitious component, the viscosity of the cementitious component of the present invention is moderate and the fluidity is good; further, the raw materials for preparing the low-clinker cement-based concrete of the present invention also add anti-cracking fibers and nano-oxides, and by limiting the ratio of the total mass percentage of anti-cracking fibers and nano-oxides to the content of the cementitious component, it is ensured that the addition of anti-cracking fibers and nano-oxides to the raw materials of the present invention helps to improve the strength and stability of the concrete. Therefore, the low-clinker cement-based concrete provided by the present invention has raw materials that reduce the use of clinker cement, and through the synergistic effect of each component, the low-clinker cement-based concrete has excellent strength and compressive properties; and the raw materials for preparing the low-clinker cement-based concrete of the present invention have low carbon emission properties and industrial environmental protection.

[0018] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0019] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a low-clinker cement-based concrete, decorative concrete component and application proposed by the present invention in combination with preferred embodiments. Its specific implementation method, structure, characteristics and effects are as follows.

[0020] The present invention provides a low-clinker cement-based concrete (hereinafter referred to as "concrete"), the raw materials of which include aggregate and cementitious components. In the cementitious components, the cementitious components include 5-30% clinker cement, 10-40% red mud, and 50-80% slag, based on the mass percentage of the cementitious components as 100%; here, the raw materials also include anti-cracking fibers and nano-oxides, the total mass ratio of the anti-cracking fibers and the nano-oxides to the mass ratio of the cementitious components is 0.02-0.15:1, preferably, in some embodiments, the total mass ratio of the anti-cracking fibers and the nano-oxides to the mass ratio of the cementitious components is 0.03-0.12:1; in some embodiments, the nano-oxides are a mixture of one or more of nano-titanium dioxide, nano-silicon dioxide, nano-zinc oxide, nano-aluminum oxide, nano-zirconium oxide, and nano-iron oxide. The red mud described in the aforementioned scheme is sintered red mud or Bayer red mud; the slag powder is water-quenched slag or air-cooled granulated blast furnace slag.

[0021] In the above scheme, the red mud in the raw material of the concrete is rich in Al2O3 and SiO2 and has strong alkalinity. Adding an appropriate amount of red mud to the cementitious component can promote the hydration of clinker cement, so that during the mixing process of the concrete raw materials of the present invention, the pores formed by the raw material components can be filled with hydration products, so that the concrete has better density and improves the mechanical strength of the concrete; it is worth noting that red mud has relatively high viscosity, and adding too much will reduce the fluidity of the cementitious component, and the compressive resistance of the prepared concrete will also be affected, while the addition of slag is beneficial to improving the fluidity of the cementitious component and the compressive resistance of the concrete. By adjusting the amount of red mud and slag added, the fluidity, compressive resistance and mechanical strength of the cementitious component of the present invention are improved; further, the concrete of the present invention also includes anti-cracking fibers and nano-oxides in its raw materials, wherein, since more red mud is added to the cementitious component of the present invention, the viscosity of the cementitious component is good, and during the mixing process of the components in the raw materials, the anti-cracking fibers can pass through the cementitious component chain The nano-oxide is connected to the aggregate to form a crack-resistant fiber network structure, which is beneficial to reinforce the concrete and improve the stability and mechanical strength of the concrete. The addition of nano-oxide is not only beneficial to accelerate the hydration speed of the cementitious component and improve the production efficiency, but also the cementitious component can use the nano-oxide as the crystal nucleus to form a network structure during the hydration process, which is beneficial to improve the stability and strength of the concrete. The nano-oxide also has a filling effect and can fill the pores and defects formed in the mixing process of the concrete. However, when the content of the anti-cracking fiber and the nano-oxide is too much, the fluidity of the cementitious component of the present invention will be affected, and then the various properties of the concrete will be affected. In order to ensure that the various properties of the concrete of the present invention are good, the present invention strictly limits the total mass percentage of the anti-cracking fiber and the nano-oxide in the raw material to the mass percentage of the cementitious component to 0.02-0.15:1. Preferably, the total mass percentage of the anti-cracking fiber and the nano-oxide to the mass percentage of the cementitious component is 0.03-0.12:1.

[0022] Based on the above, the concrete described in the present invention reduces the use of clinker cement in its raw materials, and the various components work synergistically, so the prepared concrete has excellent strength and compressive properties, and the raw materials of the concrete described in the present invention have low carbon emission properties and industrial environmental protection.

[0023] In the above scheme, in some embodiments, it is preferred that the mass percentage of Al2O3 in the red mud is 8-25%, and the mass percentage of SiO2 is 15-30%; the clinker cement is silicate clinker cement; the slag is water-quenched slag; under this condition, the compatibility of each component is better, and it helps to ensure that the prepared concrete has excellent performance. If the mass percentage of Al2O3 and SiO2 in the red mud is too low, the red mud will have a weak effect on promoting the hydration of the clinker cement. If the mass percentage of Al2O3 and SiO2 in the red mud is too high, the hydration of the cementitious component may be excessive, and when there are too many hydrates in the concrete formed after the raw materials are mixed, on the one hand, it is not conducive to the rapid drying of the concrete, and on the other hand, it may also reduce the compressive resistance and mechanical strength of the concrete.

[0024] In order to make the anti-cracking fiber and nano-oxide compatible with other raw materials, the anti-cracking fiber can be firmly linked to the aggregate through the gelling component of the present invention, and reduce the influence of the anti-cracking fiber and the nano-oxide on the fluidity of the gelling component, in some embodiments of the present invention, the anti-cracking fiber is selected from at least one of polypropylene fiber, polyvinyl alcohol fiber and basalt fiber; the nano-oxide includes nano-titanium dioxide and / or nano-silicon dioxide.

[0025] In order to enable the anti-cracking fibers to form an anti-cracking fiber network structure during the raw material mixing process, the anti-cracking fiber network structure can reinforce all aggregate components to ensure good stability of the concrete component. In some embodiments of the present invention, the ratio of the mass of the aggregate to the mass of the anti-cracking fiber is 64 to 520:1.

[0026] In order to mix the raw material components evenly and form a more complete and stable anti-cracking fiber network structure in the concrete to ensure the stability and mechanical properties of the prepared concrete, in some embodiments of the present invention, the aggregate consists of coarse aggregate and fine aggregate; the coarse aggregate is crushed stone and meets the continuous grading requirements, and its particle size range is 5 to 25 mm; the fine aggregate is machine-made sand or river sand, and its fineness modulus is 2.4 to 2.8; the anti-cracking fiber length is 6 to 25 mm; further preferably, in some embodiments, the mass of the coarse aggregate with a particle size of 5 mm≤D1≤10 mm is m1, and the mass of the coarse aggregate with a particle size of 10 mm<D2≤25 mm is m2; the ratio of m1 to m2 is 0.9 to 1.1:1.

[0027] In the aforementioned scheme, in order to enable the nano-oxide to fully fill the pores and defects formed during the mixing process of the raw materials, and to avoid excessive aggregation of the nano-oxide affecting the fluidity of the cementitious component and aggregation on the aggregate surface affecting the linking effect between the anti-cracking fiber and the aggregate, in some embodiments of the present invention, the particle size range of the nano-oxide is preferably 1 to 500 nm; the mass percentage of the anti-cracking fiber is m3, the mass percentage of the nano-oxide is m4, and the ratio of m3 to m4 is 1 to 3:1; further preferably, the ratio of m3 to m4 is 1 to 2.5:1.

[0028] Further preferably, in some embodiments, the concrete comprises, by weight percentage:

[0029] 8-22% cementitious component, 30-56% coarse aggregate, 25-52% fine aggregate, 2-9% water, 0.1-1.3% water reducing agent, 0.03-0.80% nano oxide, 0.15-1.30% anti-cracking fiber.

[0030] The above-mentioned scheme limits the content of each component in the raw materials so that during the process of preparing concrete from the raw materials provided by the present invention, the anti-cracking fibers can be better linked to the aggregate through the cementitious components described in the present invention, thereby reinforcing and stabilizing the concrete and improving the stability and strength of the concrete. The concrete components prepared under this condition have good density, good stability, and excellent mechanical strength.

[0031] Preferably, in the aforementioned concrete, the water reducer is selected from at least one of a polycarboxylate water reducer, a naphthalene-based water reducer and an aminosulfonate water reducer, which is beneficial for the concrete of the present invention to have a suitable drying speed, good concrete stability and excellent mechanical properties.

[0032] The present invention also provides a decorative concrete component, which includes the concrete described in the above scheme and has excellent low-carbon emission properties and good mechanical properties.

[0033] The low-clinker cement-based concrete or decorative concrete component described in the aforementioned solution of the present invention can be used in the fields of landscape decoration, bridge construction, transportation construction, and building construction.

[0034] The present invention also provides a building, which comprises the decorative concrete component described in the above scheme.

[0035] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0036] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0037] The coarse aggregate used in the embodiments and comparative examples of the present invention is crushed stone and meets the continuous grading requirements; the fine aggregate is machine-made sand (whose fineness modulus is 2.4-2.8); the red mud is Bayer red mud; and the slag powder is water-quenched slag powder.

[0038] Example 1

[0039] This embodiment provides a low-clinker cement-based concrete and a decorative concrete component. The composition ratios of the concrete components are shown in Table 1. The preparation method is as follows:

[0040] 1) Material pretreatment

[0041] Cementitious component: Weigh the raw materials, which contain 10% red mud, 70% slag, and 20% clinker cement (Silicate clinker cement) in terms of mass percentage; the mass percentage of Al2O3 in the red mud is 10%, and the mass percentage of SiO2 is 20%; wherein the nano-oxide used is nano-titanium dioxide, and the nano-oxide is pretreated by ultrasonication to make it evenly dispersed.

[0042] The components in the gelling component raw materials are mixed and stirred evenly to form a gelling component.

[0043] 2) Preparation of decorative concrete components

[0044] Raw material preparation: weigh the raw materials according to the mass fractions of cementitious components, coarse aggregate, fine aggregate, water, reducing agent (polycarboxylic acid water reducer), nano titanium dioxide (nano oxide particle size range is 1 to 500 nm), and anti-cracking fiber (anti-cracking fiber is polypropylene fiber, and the fiber length range is 6 to 25 mm) as described in Table 1.

[0045] The components are mixed and stirred evenly, and injection molded to obtain a decorative concrete component. In the decorative concrete component, in terms of mass percentage, the mass of coarse aggregate with a particle size of 5mm≤D1≤10mm is m1, and the mass of coarse aggregate with a particle size of 10mm<D2≤25mm is m2; the ratio of m1 to m2 is 1:1; the content of anti-cracking fiber is m3, the content of nano oxide is m4, and the ratio of m3 to m4 is 2:1.

[0046] The decorative concrete component prepared in this embodiment was subjected to strength test, and the test method was based on GB / T50081 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The test results are shown in Table 2.

[0047] Example 2

[0048] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, the remaining steps and parameters are the same as those of embodiment 1, and the detection indicators and methods are the same as those of embodiment 1.

[0049] Example 3

[0050] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, and the ratio of m3 to m4 is 2.5:1; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0051] Example 4

[0052] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, and the ratio of m3 to m4 is 20:1; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0053] Example 5

[0054] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, and the ratio of m3 to m4 is 1.3:1; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0055] Example 6

[0056] The difference between this embodiment and embodiment 1 is that the distribution ratio of each group in the raw materials of this embodiment is as shown in Table 1, and the ratio of m3 to m4 is 0.5:1; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0057] Example 7

[0058] The difference between this embodiment and embodiment 1 is that the distribution ratio of each component in the raw materials of this embodiment is as shown in Table 1, the ratio of m3 to m4 is 2.5:1; the water reducer uses aminosulfonate water reducer; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0059] Example 8

[0060] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1; and the anti-cracking fiber used in the present invention is polyvinyl alcohol fiber with a fiber length range of 6 to 20 mm. The remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0061] Example 9

[0062] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1; and the anti-cracking fiber used in the present invention is basalt fiber with a fiber length range of 6 to 22 mm. The remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0063] Example 10

[0064] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1, the particle size range of the nano oxide is 1 to 600 nm, and the length range of the anti-cracking fiber is 5 to 35 mm; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0065] Embodiment 11

[0066] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1; the nano-oxide is nano-silicon dioxide, and the particle size range of the nano-oxide is 1 to 450 nm; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0067] Example 12

[0068] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1; the cementitious component includes 25% red mud, 50% slag, and 25% clinker cement; the mass percentage of Al2O3 in the red mud is 8%, and the mass percentage of SiO2 is 15.0%; the ratio of m1 to m2 is 0.9:1, and the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0069] Embodiment 13

[0070] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1; the gelling component comprises 5% red mud, 80% slag, and 15% clinker cement; the nano oxide is nano zinc oxide; the mass percentage of Al2O3 in the red mud is 25%, and the mass percentage of SiO2 is 30%; the ratio of m1 to m2 is 1:1, and the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0071] Embodiment 14

[0072] The difference between this embodiment and embodiment 1 is that the distribution ratio of each component in the raw materials of this embodiment is as shown in Table 1; the cementitious component comprises 20% red mud, 50% slag, and 30% clinker cement; the mass percentage of Al2O3 in the red mud is 25%, and the mass percentage of SiO2 is 30%; the remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0073] Embodiment 15

[0074] The difference between this embodiment and embodiment 1 is that the proportions of the components in the raw materials of this embodiment are as shown in Table 1; the total mass ratio of the anti-cracking fiber and the nano-oxide to the mass ratio of the gelling component is 0.18:1. The remaining steps and parameters are the same as those in embodiment 1, and the detection indicators and methods are the same as those in embodiment 1.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that the only difference between Comparative Example 1 and Example 1 is that nano titanium dioxide is not added, and the remaining steps and parameters are the same as those in Example 1, and the detection indicators and methods are the same as those in Example 1.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that the difference between Comparative Example 2 and Example 1 is that the anti-cracking fiber is not added; the remaining steps and parameters are the same as Example 1, and the detection indicators and methods are the same as Example 1.

[0079] Table 1 shows the contents of various components of concrete raw materials provided by the embodiments and comparative examples, wherein α is the mass percentage of clinker cement in the cementitious component; κ is the mass ratio of the total mass of the anti-cracking fiber and the nano-oxide to the mass of the cementitious component; m1 is the mass of coarse aggregate with a particle size of 5mm≤D1≤10mm, m2 is the mass of coarse aggregate with a particle size of 10mm<D2≤25mm, m3 is the mass percentage of the anti-cracking fiber in the concrete, and m4 is the mass percentage of the nano-oxide in the concrete; Table 2 shows the performance index test results of the decorative concrete components prepared in the embodiments and comparative examples.

[0080] Table 1 Raw material components and proportions of low-clinker cement-based concrete in various embodiments and comparative examples (parts)

[0081]

[0082]

[0083] Table 2 Splitting tensile strength and compressive strength of decorative concrete components prepared in Examples and Comparative Examples

[0084] Group 28d splitting tensile strength / MPa 28d compressive strength / MPa Example 1 6.8 58.5 Example 2 7.8 62.6 Example 3 6.9 63.1 Example 4 6.0 55.5 Example 5 8.2 68.5 Example 6 5.6 56.6 Example 7 8.6 64.5 Example 8 7.4 61.6 Example 9 7.9 62.0 Example 10 7.2 59.6 Embodiment 11 6.8 58.0 Example 12 6.9 59.0 Embodiment 13 6.3 56.0 Embodiment 14 6.5 57.6 Embodiment 15 5.3 50.2 Comparative Example 1 5.1 40.1 Comparative Example 2 3.1 45.5

[0085] From the above data, it can be seen that the decorative concrete components prepared by the method described in the present invention in Examples 1 to 14 have a 28d compressive strength of 55.5-68.5 MPa and a 28d splitting tensile strength of 5.6-8.6 MPa, which indicates that the decorative concrete components of the present invention still have excellent mechanical properties even if the amount of clinker cement used is reduced; in Example 15, since the total mass ratio of the added anti-cracking fiber and the nano-oxide to the mass of the cementitious component is not within the required range of the present invention, the performance of the prepared decorative concrete component is reduced.

[0086] By comparing Comparative Examples 1 and 2 with the embodiment, it can be seen that if the concrete provided by the present invention lacks anti-cracking fibers and nano-oxide components, the compressive strength and splitting tensile strength of the prepared decorative concrete components are much lower than those in the embodiment. It can be seen that nano-oxides and anti-cracking fibers have a synergistic effect, and the simultaneous use of the two significantly improves the compressive strength and splitting tensile strength of the decorative concrete components.

[0087] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A low-clinker cement-based concrete, whose raw materials include aggregate and cementitious components, characterized in that: Taking the mass percentage of the cementitious component as 100%, the cementitious component includes 5-30% clinker cement, 10-40% red mud, and 50-80% slag; the concrete also includes anti-cracking fiber and nano-oxide, and the mass ratio of the total mass of the anti-cracking fiber and the nano-oxide to the mass of the cementitious component is 0.02-0.15:

1.

2. The concrete according to claim 1, characterized in that The mass percentage of Al2O3 in the red mud is 8-25%, and the mass percentage of SiO2 is 15-30%; the clinker cement is silicate clinker cement; and the slag is water-quenched slag.

3. The concrete according to claim 2, characterized in that: The anti-cracking fiber is selected from at least one of polypropylene fiber, polyvinyl alcohol fiber and basalt fiber; the nano-oxide includes nano-titanium dioxide and / or nano-silicon dioxide.

4. The concrete according to claim 3, characterized in that The mass ratio of the aggregate to the anti-cracking fiber is 64-520:

1.

5. The concrete according to any one of claims 1 to 4, characterized in that: The aggregate comprises coarse aggregate and fine aggregate; the particle size of the coarse aggregate is in the range of 5 to 25 mm; the fine aggregate is machine-made sand or river sand, and its fineness modulus is 2.4 to 2.8; and the length of the anti-cracking fiber is 6 to 25 mm.

6. The concrete according to claim 5, characterized in that The mass of the coarse aggregate with a particle size of 5mm≤D1≤10mm is m1, and the mass of the coarse aggregate with a particle size of 10mm<D2≤25mm is m2; the ratio of m1 to m2 is 0.9-1.1:

1.

7. The concrete according to claim 6, characterized in that The particle size of the nano oxide is in the range of 1 to 500 nm; the mass percentage of the anti-cracking fiber is m3, the mass percentage of the nano oxide is m4, and the ratio of m3 to m4 is 1 to 3:

1.

8. The concrete according to claim 7, characterized in that Calculated by mass percentage, it includes: 8-22% of cementitious components, 30-56% of coarse aggregate, 25-52% of fine aggregate, 2-9% of water, 0.1-1.3% of water reducing agent, 0.03-0.80% of nano oxide, and 0.15-1.30% of anti-cracking fiber.

9. A decorative concrete component, characterized in that: It comprises the concrete according to any one of claims 1 to 8.

10. A building, characterized in that: It comprises the decorative concrete component according to claim 9.

Citation Information

Patent Citations

  • Ultra-high-performance decorative concrete and preparation method thereof

    CN108264289A

  • Low-clinker cement as well as preparation method and application thereof

    CN111847921A

  • Non-structural silicon-aluminum cementing material concrete as well as preparation method and application thereof

    CN119161137A

  • Low-carbon high-durability concrete

    CN119191803A